Descriptive analysis on perception hibah as a property dispute resolution tool among staff in SK Balok Baru - Norlizal, Norain Husna (2024)
The current study assesses the perception of SK Balok Baru staff on hibah as an instrument in settling property disputes. This study utilizes a quantitative approach through a questionnaire given to 44 respondents. The results of the study described that a large number of respondents understand the concept of hibah, but there are several factors that influence respondents not to choose hibah as an alternative in resolving property disputes, including lack of knowledge about hibah. The result of this study indicates that educational programs on hibah have to be enhanced to inspire its utilization as one of the tools for amicable and harmonious resolutions of property disputes. It also means that with better awareness, hibah is able to reduce property disputes among the community.